Asas Imparsial dalam Proses Hukum Acara Pidana di Indonesia - Febiola Febiola; Cintya Thilawatil Fitri; Enjely Suci Pratiwi; Ikhsan Wafdullah; Siti Hardiyani; Lysa Angrayni (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The principle of impartiality is an important element of criminal procedure law, playing a crucial role in ensuring a fair and impartial judicial process. This article discusses the importance of impartiality in criminal proceedings, both in terms of the concept and the impact of violating the principle in the justice system. The principles of fairness and impartiality require judges and law enforcers to be neutral, and not influenced by external pressure in making decisions. Implementation of the principle of impartiality ensures that every individual is treated equally in the eyes of the law, in accordance with the principle of equality before the law. Violation of this principle can result in injustice, cause harm to the parties involved, and reduce public trust in the justice system. This confirms that the principle of impartiality is not only an ethical norm, but also the foundation of substantive justice in criminal law. Therefore, upholding the principles of fairness in criminal proceedings is crucial to maintaining the integrity and fairness of the justice system in Indonesia. To improve the implementation of the principle of impartiality, various strategic steps need to be taken, such as providing intensive training to judicial officers, strengthening supervisory mechanisms, increasing transparency in the judicial process, and strengthening the enforcement of professional ethics. In addition, active public participation in the judicial process must be encouraged.